IMPROVING STUDENT’S VOCABULARY THROUGH FOLDING PAPER METHOD FOR STUDENTS AT SMA MIFTAHUL ANWAR PAMEKASAN - Fitrah Yuliawati; Siti Faizah Wahyuni (IKIP Siliwangi, 2024)
The aim of the research is to increase students understanding and memorization of English vocabulary by using the folding paper method, namely making several character shapes from origami paper. The research conducted at 11th grade students in SMA Miftahul Anwar Klompek Pamoroh Pamekasan. This research use Classroom Action Research (CAR) by using planning, implementing, observing action and reflecting on data collected from teaching and learning processes and student’s evaluations. Based on the test results in cycle I and cycle II, the mean score of the preliminary study was 61, 5 and the percentage score was 30%. The mean score of cycle I is 68, 25 and the percentage score is 60%. The mean score of cycle II is 76 and the percentage score of 90%. This means that students have improvement from preliminary, cycle I until cycle II. In conclusion, it is proved that studying with the folding paper method can improve student’s ability to understand and memorize English vocabulary.